2018
DOI: 10.1186/s12913-018-3349-6
|View full text |Cite
|
Sign up to set email alerts
|

Cultural orientations and information systems success in public and private hospitals: preliminary evidences from Italy

Abstract: BackgroundThe effective adoption and use of digital and computerized systems and records in hospitals are crucial for increasing the overall quality, safety and outcomes of any national health community. Prior research found that hospitals’ dominant cultural orientation affects the adoption of new technology. However, the organizational culture of hospitals can greatly vary between public and private hospitals. Thus, the ownership type of the hospital is likely to affect, to some extent, the aforementioned rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…In conclusion, these scholars' findings correspond to the strong correlation, which the current study found, in which management of employees is a positively effective factor in strategy implementation. Specifically supporting the above view, the findings indicate that both private and public sectors need systems and hence the necessity of a hierarchical culture in their effective strategy implementation in organizations (Lepore, Metallo, Schiavone, & Landriani, 2018). Other studies also support the significance of a hierarchical culture with a strong relationship to strategy implementation concluding that a hierarchical culture plays a big role in any change management giving hints to significant role models in leadership changes (Al-Ali et al, 2017).…”
Section: Discussionsupporting
confidence: 56%
“…In conclusion, these scholars' findings correspond to the strong correlation, which the current study found, in which management of employees is a positively effective factor in strategy implementation. Specifically supporting the above view, the findings indicate that both private and public sectors need systems and hence the necessity of a hierarchical culture in their effective strategy implementation in organizations (Lepore, Metallo, Schiavone, & Landriani, 2018). Other studies also support the significance of a hierarchical culture with a strong relationship to strategy implementation concluding that a hierarchical culture plays a big role in any change management giving hints to significant role models in leadership changes (Al-Ali et al, 2017).…”
Section: Discussionsupporting
confidence: 56%
“…Problem of endogeneity may arise in cross-sectional analyses if there are unobserved factors that are correlated with the measurement of private hospital expansions and the occurrences of medical malpractice lawsuits. For example, cultural factors may affect patients' choices between private and public hospitals [27], as well as choice of health insurance. Thus, cultural factors may have impacts on health care market.…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted a positivist approach, involving a hypothesis based on the theoretical framework in testing the hypothesis. The philosophy as applied in the study was dictated by observations and descriptions in the field without any influence of the phenomenon as supported by [28]. As pointed out by [30], the study eliminated any possible subjectivism and ensured all activities were objective while collecting data.…”
Section: Methodsmentioning
confidence: 99%